2011
DOI: 10.3390/molecules161210619
|View full text |Cite
|
Sign up to set email alerts
|

The in Vitro Structure-Related Anti-Cancer Activity of Ginsenosides and Their Derivatives

Abstract: Panax ginseng has long been used in Asia as a herbal medicine for the prevention and treatment of various diseases, including cancer. The current study evaluated the cytotoxic potency against a variety of cancer cells by using ginseng ethanol extracts (RSE), protopanaxadiol (PPD)-type, protopanaxatriol (PPT)-type ginsenosides fractions, and their hydrolysates, which were prepared by stepwise hydrolysis of the sugar moieties of the ginsenosides. The results showed that the cytotoxic potency of the hydrolysates … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
55
0
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 79 publications
(57 citation statements)
references
References 15 publications
(14 reference statements)
1
55
0
1
Order By: Relevance
“…The tumor suppressive ability of G-Rh2 is related to the inhibition of cell proliferation and metastasis, and induction of apoptosis . However, studies using different cell line models have reported conflicting data (Choi et al, 2011;Dong et al, 2011;Chung et al, 2013;Tang et al, 2013;Fatmawati et al, 2014;Guo et al, 2014;You et al, 2014a). We previously reported that G-Rh2 can inhibit the proliferation of human lung adenocarcinoma A549 cells as well as cause cell cycle arrest in the G1 phase in a dose-dependent manner.…”
Section: Introductionmentioning
confidence: 99%
“…The tumor suppressive ability of G-Rh2 is related to the inhibition of cell proliferation and metastasis, and induction of apoptosis . However, studies using different cell line models have reported conflicting data (Choi et al, 2011;Dong et al, 2011;Chung et al, 2013;Tang et al, 2013;Fatmawati et al, 2014;Guo et al, 2014;You et al, 2014a). We previously reported that G-Rh2 can inhibit the proliferation of human lung adenocarcinoma A549 cells as well as cause cell cycle arrest in the G1 phase in a dose-dependent manner.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, the pharmacological effects of PPD are similar to or stronger than those of Rh2 and Rg3 (Hasegawa et al, 2000;Lee et al, 2000;Popovich & Kitts, 2004). Previous studies indicated that PPD showed powerful pleiotropic anti-cancer effects in several cancer cell lines and the capability of inhibiting metastasis (Li et al, 2006;Liu et al, 2007;Dong et al, 2011;Zhu et al, 2011), thus becomes a potential therapeutic agent in the prevention and treatment of cancer (Popovich & Kitts, 2002;Yu et al, 2007;Usami et al, 2008). As such, it is currently undergoing phase I clinical trials in China.…”
Section: (S)-protopanaxadiol (Ppd) Is Mainly Derived From Ginsengmentioning
confidence: 99%
“…16 For example, the less polar ginsenosides demonstrate higher cytotoxic activity against several cancer cells. 14,17 Despite established anti-neoplastic properties of ginsenosides, a link between ginseng sapogenins structure and its anticancer activity as well as its mode of action in TN breast cancer has not been established. Hence, we designed this study to compare the anti-cancer effects of PPD, PPT, 2H-PPD, and 2H-PPT in TN breast cancer by using MDA-MB-231 cells.…”
mentioning
confidence: 99%